Implementation of Character Education Values in Elementary School Age Students in Nurul Huda Islamic Boarding School - Yuni Suprapto; Ihdya Putri A; Akhmad Nurkholis (Research and Innovation in Social Science Education Journal (RISSEJ), 2024)
purpose of this study is to identify and analyze the inculcation of character education, as well as to identify and analyze the impact of character for education on students of elementary school at the Nurul Huda Islamic Boarding School. This type of research is qualitative, with the subject being caregivers, administrators, and the person in charge of the Nurul Huda Islamic Boarding School. Data collection techniques using observation, interviews, and documentation. The data analysis technique uses data reduction, data display, and conclusions. The results showed that the cultivation of character education at Islamic Boarding School of Nurul Huda Pesanggrahan consisted of character values ​​believing in the existence of Almighty God and always obeying His commands, tolerance, discipline, responsibility, developing self-potential, love and compassion, respect, etiquette, courtesy, honesty, and independence. The impact that arises is the increasing understanding and ability of students in applying character values, believing in the existence of God Almighty and always obeying His commands, tolerance, discipline, responsibility, developing self-potential, love and compassion, respect, manners and courtesy, honesty and independence.